Multi objective optimization in machining of Inconel 718 using taguchi method. (2021) - Senthilkumar, K.M.; Thirumalai, R.; Selvam, T.A.; Natarajan, A.; Ganesan, T.
Abstract: Nickel based super alloys find wide application in industries like aerospace engine, nuclear reactors and other high temperature applications etc. Inconel 718 alloy is well suited for high temperature applications with excellent mechanical strength. Due to high strength it is difficult to machine. Many researchers were concentrated on optimization of various machining process for single response criteria. It is very difficult to select an optimal parameter for multi response criteria. To overcome this problem multi objective optimization technique is used to find optimal setting of machining parameter in milling of Inconel 718 alloy. In this paper, the effects of various machining parameters like cutting speed, feed, and depth on tool wear, MRR and surface roughness are studied. Three different coated carbide inserts are used for machining process and to perform multi objective optimization which would provide minimum tool wear and surface roughness and maximum MRR.